2018
DOI: 10.5206/cjsotl-rcacea.2018.1.5
|View full text |Cite
|
Sign up to set email alerts
|

As Good or Better than Commercial Textbooks: Students’ Perceptions and Outcomes from Using Open Digital and Open Print Textbooks

Abstract: The increase in the cost of college textbooks together with the proliferation of digital content and devices has inspired the development of open textbooks, open educational resources that are free, openly licensed, and often peer-reviewed. Although several published studies have investigated the impact of open textbook adoption on educational outcomes, none have separated the effects of textbook openness and format and only two have taken place in Canada (Hendricks, Reinsberg, & Rieger, 2017; Jhangiani &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
106
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(128 citation statements)
references
References 23 publications
10
106
0
2
Order By: Relevance
“…However, there were no statistically significant differences between textbooks in student perceptions of items relating to everyday life examples and difficulty. The lack of difference in learning performance by textbook type is consistent with previous quasi-experimental research comparing open textbooks with commercial textbooks (e.g., Hendricks et al, 2017;Clinton, 2018;Jhangiani et al, 2018;Lawrence and Lester, 2018;see Hilton, 2016, for a systematic review; see Clinton and Khan, 2019, for a meta-analysis). However, a key difference is that in this experiment, it was certain that everyone had access to the excerpt of the textbook.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, there were no statistically significant differences between textbooks in student perceptions of items relating to everyday life examples and difficulty. The lack of difference in learning performance by textbook type is consistent with previous quasi-experimental research comparing open textbooks with commercial textbooks (e.g., Hendricks et al, 2017;Clinton, 2018;Jhangiani et al, 2018;Lawrence and Lester, 2018;see Hilton, 2016, for a systematic review; see Clinton and Khan, 2019, for a meta-analysis). However, a key difference is that in this experiment, it was certain that everyone had access to the excerpt of the textbook.…”
Section: Discussionsupporting
confidence: 86%
“…For example, after high school grade point averages are considered, course grades for students in introduction to psychology courses with commercial or open textbooks were similar (Clinton, 2018). Consistent findings were observed in another study examining introduction to psychology courses in which students in courses with open or commercial textbooks, who had comparable levels of prior psychology knowledge based on pretest findings, had similar exam grades (Jhangiani et al, 2018). In physics, students earned similar grades and experienced similar changes in attitudes toward science in courses with commercial and open textbooks (Hendricks et al, 2017).…”
Section: Literature Reviewsupporting
confidence: 68%
See 1 more Smart Citation
“…these textbooks have been adopted by over 400 faculty across 42 BC institutions in more than 1650 course sections, with an estimated total savings to students of over $5.5 million (BCcampus, 2017). In addition to these significant cost savings, BC students assigned OER have been shown to perform the same as or better than those assigned commercial textbooks (Hendricks et al, 2017;Jhangiani, Dastur, LeGrand, & Penner, in press), a consistent finding in the research literature (Hilton, 2016).…”
Section: Introductionsupporting
confidence: 63%
“…Jhangiani and Jhangiani (2017) similarly found that 44% of students at post-secondary institutions in British Columbia preferred to use print material exclusively in class, while 16% preferred digital only. Jhangiani, Dastur, Le Grand, and Penner (2018) also focused on the print versus digital question in their recent study and found that students rated print OER more highly than digital OER or traditional course materials. These findings substantiated other studies that have not focused on OER exclusively but showed a preference among students for reading print as opposed to digital texts, although course outcomes did not differ markedly between the formats.…”
Section: Literature Reviewmentioning
confidence: 99%